Inheritance For Children Outside of Marriage - Alfa Nadia Paparang (Estudiante Law Journal, 2026)
Abstract: This study aims to determine the division of inheritance for children outside of marriage. The research methods used are normative research and use a statutory research approach and a case approach and descriptive analysis. The results of this study show that based on the provisions of the Civil Code, an out-of-wedlock child is considered not to have any legal relationship with his parents if there is no recognition from his father or mother, thus if the out-of-wedlock child is recognized, he can inherit the inheritance from the parents who recognize it, and of course the division of inheritance based on the law. However, on the one hand, also with the enactment of the Marriage Law, namely Law No. 16 of 2019 concerning Marriage, even unrecognized extramarital children automatically have a civil relationship with their mother and their mother's family. However, not with his Father as long as it cannot be corroborated by an authentic deed.